Thermodynamic properties of benzene adsorbed in activated carbons and multi-walled carbon nanotubes - Gauden, P.; Terzyk, A.; Rychlicki, G.; Kowalczyk, Poitr; Lota, K.; Raymundo-Pinero, E.; Frackowiak, E.; Beguin, F. (Elsevier, 2006)
The efficiency of multi-walled carbon nanotubes (MWNTs) and traditional activated carbons for benzene adsorption is studied. Benzene adsorption isotherms and the related values of the calorimetric adsorption enthalpy at 298 K are used to calculate the entropy and the state of the adsorbed molecules. The analysis of the experimental data leads to the conclusion that both thermodynamic functions are related to the kind of porosity present in the studied materials. Our results also show that in the case of MWNTs the adsorption between the tubes is a very important effect which determines the mechanism of this process.